IT Management: The art of managing IT based on a solid framework leveraging the company's political ecosystem - Pilorget, Lionel; Schell, Thomas (Springer, 2018)
This book focuses on the art of managing IT. A simple and robust framework is proposed to describe and to structure the essential elements of IT management. The authors pay particular attention to didactic aspects in order to facilitate the retention of models presented as well as to promote reflection on the subjects introduced.